Spatial Patterns and Mechanisms for Terrestrial Ecosystem Carbon Fluxes in the Northern Hemisphere - Chen, Zhi (Springer Theses, Recognizing Outstanding Ph.D. Research, 2018)
This book systematically illustrates the underlying mechanisms of spatial variation in ecosystem carbon fluxes. It presents the regulation of climate pattern, together with its impacts on ecosystem traits, which yields new insights into the terrestrial carbon cycle and offers a theoretic basis for large-scale carbon pattern assessment. By means of integrated analysis, the clear spatial pattern of carbon fluxes (including gross primary production, ecosystem respiration and net ecosystem production) along latitudes is clarified, from regions to the entire Northern Hemisphere. Temperature and precipitation patterns play a vital role in carbon spatial pattern formation, which strongly supports the application of the climate-driven theory to the Northern Hemisphere. With regard to the spatial pattern, the book demonstrates the covariation between production and respiration, offering new information to promote current respiration model development. Moreover, it reveals the high carbon uptake of subtropical forests across the East Asian monsoon region, which challenges the view that only mid- to high-latitude terrestrial ecosystems are principal carbon sink regions, and improves our understanding of carbon budgets and distribution. .